The socialization of modality capital in sign language ecologies: A classroom example - Singleton, Jenny L.; Crume, Peter K. (Frontiers in Psychology, 2022)
Gaze behavior is an important component of children’s language, cognitive, and sociocultural development. This is especially true for young deaf children acquiring a signed language – if they are not looking at the language model, they are not getting linguistic input. Deaf caregivers engage their deaf infants and toddlers using visual and tactile strategies to draw in, support, and promote their child’s visual attention; we argue that these caregiver actions create a developmental niche that establishes the visual modality capital their child needs for successful sign language learning. But most deaf children do not have deaf signing parents (reportedly over 90%) and they will need to rely on adult signing teachers if they are to acquire a signed language at an early age. This study examines classroom interactions between a Deaf teacher, her teacher’s aide, and 6 deaf preschoolers to document the teachers’ “everyday practices” as they socialize the gaze behavior of these children. Utilizing a detailed behavioral and linguistic analysis of two video-recorded book-sharing contexts, we present data summarizing the teacher’s attention-getting actions directed toward the children and the discourse-embedded cues that signal the teacher’s expectations for student participation in the signed conversation. We observed that the teacher behaviors differed according to the parent status of the deaf preschooler (Deaf parents vs. hearing parents) suggesting that Deaf children of Deaf parents arrive to the preschool classroom with well-developed self-regulation of their attention or gaze. The teachers also used more physical and explicit cueing with the deaf children of hearing parents – possibly to promote their ability to leverage the visual modality for sign language acquisition. We situate these socialization patterns within a framework that integrates notions of intuitive or indigenous practices (Humphries 2004; Papoušek and Papoušek 1987), developmental niche (Super and Harkness 1986, 2002), and modality capital. Implications for early childhood deaf education are also discussed.